Predictive value of visual evoked potentials, relative afferent pupillary defect, and orbital fractures in patients with traumatic optic neuropathy - Tabatabaei SA (Dove Medical Press, 2011)
Seyed Ali Tabatabaei1, Mohammad Soleimani2, Mahdi Alizadeh1, Morteza Movasat1, Mohammad Reza Mansoori1, Zakieh Alami1, Alireza Foroutan2, Mahmood Joshaghani2, Saeid Safari2, Arzhang Goldiz21Farabi Eye Research Centre, Farabi Eye Hospital, Tehran University of Medical Sciences, Tehran, Iran; 2Iran Eye Research Centre, Rassul Akram Hospital, Tehran, IranBackground: The purpose of this study was to determine the predictive value of flash visual-evoked potentials (VEP), relative afferent pupillary defect, and presence of orbital fractures in patients with traumatic optic neuropathy.Methods: A prospective study was conducted in 15 patients with indirect traumatic optic neuropathy. All patients underwent a thorough ophthalmic examination. Initial visual acuity, final visual acuity, and relative afferent pupillary defect were determined, and visual acuity was converted into logMAR units. We performed flash VEP and an orbital computed tomography scan in all patients.Results: There was a good correlation between relative afferent pupillary defect and final visual acuity (r = −0.83), and better initial visual acuity could predict better final visual acuity (r = 0.92). According to findings from flash VEP parameters, there was a relationship between final visual acuity and amplitude ratio of the wave (r = 0.59) and latency ratio of the wave (r = −0.61). Neither primary visual acuity nor final visual acuity was related to the presence of orbital fractures in the orbital CT scan.Conclusion: Patients with traumatic optic neuropathy often present with severe vision loss. Flash VEP, poor initial visual acuity, and higher grade of relative afferent pupillary defect could predict final visual acuity in these patients. Presence of orbital fracture was not a predictive factor for primary visual acuity or final visual acuity.Keywords: visual acuity, flash VEP, RAPD, orbital fracture, CT scan